Aquatic activity learning model the fun games-based on breast stroke swimming in bachelor students - Roma Irawan; Monica Dara Pratiwi; Syahrastani Syahrastani; Muhammad Sazeli Rifki; Ardo Okilanda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The Studi Purpose. Students have difficulty in doing swimming movements because they do not know the good sequence of movements. The purpose of this research is to help students learn to swim in an easy and fun way so they can do breaststroke swimming. Material and Methods. Effectivenes model fun games with 51 students as research subjects from the Faculty of Sports Science, UNP. The data collection instrument used expert validation questionnaires, documentation, and breaststroke swimming tests. The data analysis technique used independent sample t test analysis and aiken rater score. Results. The research findings show that fun games effectively improve students' breaststroke swimming ability. In the t-test obtained experimental group there is a difference. Conclusions. that there is a significant difference between the experimental class and the control class where using an aquatic learning model based on breaststroke swimming fun games has a greater influence on students' breaststroke swimming ability compared to those who do not use. Swimming learning is easier if done with fun games this is very good if the coach applies it.